Study on drawing die radius to load and thinning pattern of aluminium alloy - Jamil, Nurul Izzati Mohamad (Universiti Sains Malaysia, 2019)
Deep drawing in square cup is very complex and associated with many defects. This is a study where the thinning pattern in the square deep drawing process by focusing on the effect of size at die corner radius was carried out. Thinning of metal is a strain pattern that takes place prior to sheet metal failure. This project shows the variation in die corner radius have an influences on the material flow. Here the load and thinning pattern on square cup drawn by deep drawing process is observed. The main features in this experiment is die corner radius and the studied material is Aluminium alloy. This project is an approach to use Universal Testing Machine (UTM) and Digital Image Correlation (DIC) as apparatus in the experiment and analyze the data using Davis software. Result found that, the material or specimen would undergo the faster deformation at small corner radius. It is concluded that, the formability of material in square corner area depends on the die corner geometry